The evaluation of the degree of Financial Inclusion in the Algerian Banking sector in the period between (2011- 2018) - bouzana, aimen; hamdouche, wafa (Journal of Research in Finance and Accounting, 2021)
The financial inclusion became one of the topics that hold the attention in the national financial and Economical activities and also one of the principal items on the Algerian banking sector schedule. This study aims at evaluating the levels of the principal financial inclusion in the Algerian banking sector in the period between (2011- 2018) to stand on the levels of the banking mediation given to the Algerian society categories. The study concludes that the contribution of the banking sector in enhancing the degree of financial inclusion the Algerian society is modest due to the slow banking mediation provided by the banking sector, the lack of progress in the banking industry, the limited levels of financial inclusion indicators and the lack of efforts by the monetary authorities to deepen their degree of inclusion